Anode, secondary battery and battery pack
Patent Information
- Application Number
- JP2023569016
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-24
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-12-24
Smart Images

Figure 0007631556000003 
Figure 0007631556000004 
Figure 0007631556000005
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE The present invention relates to a negative electrode, a secondary battery, and a battery pack. [Background technology]
[0002] Due to the rapid development of electronics technology in recent years, electronic devices are becoming smaller and lighter. There is a strong demand for secondary batteries, which are the driving or backup power sources for such electronic devices, that are small, lightweight, and have a high energy density. 2 Due to the demand for reducing CO2 emissions, there is an urgent need to develop a larger capacity power storage system for electric vehicles, nighttime power storage at home, etc. Lithium secondary batteries, which have a high volumetric density, have been attracting attention as a new secondary battery that can meet such demands.
[0003] Lithium titanate, which is used as an electrode material for lithium secondary batteries, is, for example, Li 4 Ti 5 O 12 The spinel-type lithium titanate represented by the chemical formula LTO is used. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 2019-169276 [Patent Document 2] Japanese Patent Application Publication No. 2008-311067 [Patent Document 3] Japanese Patent Application Publication No. 2012-178327 [Patent Document 4] Japan Special Publication No. 2019-535110 Summary of the Invention [Problem to be solved by the invention]
[0005] Compared with lithium secondary batteries using general carbon materials as negative electrode active materials, secondary batteries using spinel-type lithium titanate as negative electrode active materials have small volume changes due to charging and discharging, so that the capacity reduction and negative electrode deterioration caused by the insertion and removal of lithium are less likely to progress. However, negative electrodes containing spinel-type lithium titanate have a large self-discharge compared to commonly used negative electrode active materials. Therefore, there was a problem that the positive electrode potential increases and the positive electrode deterioration progresses when the charge and discharge cycles are repeated.
[0006] In addition, the occurrence of self-discharge on the surface of the negative electrode is accompanied by the formation of a coating due to a side reaction between the active material particles and the electrolyte. When the charge-discharge cycle is repeated, the resistance in a low-temperature environment tends to increase more easily than the room-temperature resistance due to the formation of this coating. In other words, a negative electrode containing spinel-type lithium titanate has a problem that the charge-discharge characteristics in a low-temperature environment are easily deteriorated.
[0007] The present invention has been made in consideration of the above circumstances, and has an object to provide a negative electrode capable of realizing a secondary battery exhibiting excellent cycle life characteristics and low-temperature characteristics, a secondary battery including this negative electrode, and a battery pack including this secondary battery. [Means for solving the problem]
[0008] According to an embodiment, a negative electrode is provided. The negative electrode includes a current collector and an active material-containing layer supported on at least a part of the current collector. The active material-containing layer includes a plurality of active material particles, a first binder that covers at least a part of the surface of the plurality of active material particles, and a second binder different from the first binder. The plurality of active material particles include lithium titanate having a spinel structure. The first binder includes at least one selected from the group consisting of polyvinylpyrrolidone, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, polyvinyl chloride, polyvinyl acetate, and polyacrylic acid. The ratio of the mass of the first binder to the mass of the plurality of active material particles is within a range of 0.05% by mass to 0.50% by mass.
[0009] According to another embodiment, a negative electrode is provided. The negative electrode includes a current collector and an active material-containing layer supported on at least a part of the current collector. The active material-containing layer includes a plurality of active material particles, a first binder that covers a part of the surface of the plurality of active material particles, a second binder different from the first binder, and an aluminum-containing coating that covers another part of the surface of the plurality of active material particles. The plurality of active material particles include lithium titanate having a spinel structure. The first binder includes at least one selected from the group consisting of polyvinylpyrrolidone, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, polyvinyl chloride, polyvinyl acetate, and polyacrylic acid. The ratio of the mass of the first binder to the mass of the plurality of active material particles is within a range of 0.01% by mass to 0.50% by mass. The ratio of the mass of aluminum contained in the aluminum-containing coating to the mass of the plurality of active material particles is within a range of 0.04% by mass to 0.30% by mass.
[0010] According to another embodiment, a secondary battery is provided, the secondary battery comprising a negative electrode according to the embodiment, a positive electrode, and an electrolyte.
[0011] According to another embodiment, a battery pack is provided, the battery pack including a secondary battery according to the embodiment. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a cross-sectional view illustrating an example of a secondary battery according to an embodiment. [Diagram 2] 2 is an enlarged cross-sectional view of a portion A of the secondary battery shown in FIG. 1. [Diagram 3] FIG. 4 is a partially cutaway perspective view illustrating a schematic diagram of another example of a secondary battery according to an embodiment. [Figure 4] 4 is an enlarged cross-sectional view of part B of the secondary battery shown in FIG. 3. [Diagram 5] FIG. 1 is a perspective view illustrating an example of a battery pack according to an embodiment. [Figure 6] FIG. 1 is an exploded perspective view illustrating an example of a battery pack according to an embodiment. [Figure 7]7 is a block diagram showing an example of an electric circuit of the battery pack shown in FIG. 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, the embodiments will be described with reference to the drawings. Note that the same reference numerals are used to designate common components throughout the embodiments, and duplicated descriptions will be omitted. Each figure is a schematic diagram for explaining the embodiments and for facilitating understanding thereof, and the shapes, dimensions, ratios, etc. may differ from those of the actual device, but these can be appropriately modified in design by taking into consideration the following explanation and known techniques.
[0014] It is believed that when the surface of the negative electrode active material is exposed, the formation of a coating due to self-discharge continues. Therefore, the formation of the coating progresses due to repeated charge-discharge cycles of the secondary battery and / or deterioration over time, and the positive electrode potential continues to increase. As a result, there is a problem that the positive electrode deteriorates and oxidizing gas is generated due to the difference in SOC (State of Charge) between the positive and negative electrodes.
[0015] According to the negative electrode of the embodiment, self-discharge on the surface of the negative electrode active material can be suppressed, and therefore an increase in the positive electrode potential can be suppressed. As a result, a secondary battery exhibiting excellent cycle life characteristics and low-temperature characteristics can be realized.
[0016] (First embodiment) According to a first embodiment, a negative electrode is provided. The negative electrode includes a current collector and an active material-containing layer supported on at least a part of the current collector. The active material-containing layer includes a plurality of active material particles, a first binder that covers at least a part of the surface of the plurality of active material particles, and a second binder different from the first binder. The plurality of active material particles include lithium titanate having a spinel structure. The first binder includes at least one selected from the group consisting of polyvinylpyrrolidone, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, polyvinyl chloride, polyvinyl acetate, and polyacrylic acid. The ratio of the mass of the first binder to the mass of the plurality of active material particles is within a range of 0.05% by mass to 0.50% by mass.
[0017] The negative electrode according to the embodiment may further include a current collector. The negative electrode is, for example, a negative electrode for a battery, a negative electrode for a secondary battery, or a negative electrode for a lithium ion secondary battery.
[0018] The active material-containing layer is a sheet-like layer that can be formed on one or both sides of the current collector. The active material-containing layer includes, for example, a plurality of active material particles, a first binder that covers at least a part of the surface of the plurality of active material particles, and a second binder different from the first binder. The active material-containing layer may further include a conductive agent.
[0019] The thickness of the active material-containing layer is not particularly limited, but is within the range of, for example, 10 μm to 120 μm. In particular, from the viewpoints of input / output characteristics and ease of electrode fabrication, a thickness of 12 μm to 70 μm is desirable.
[0020] The active material particles include lithium titanate having a spinel structure. The mass ratio of the lithium titanate having a spinel structure to the active material particles may be 50% by mass or more. The ratio may be 70% by mass or more, 80% by mass or more, 90% by mass or more, or 100% by mass. That is, the active material particles may be composed only of lithium titanate having a spinel structure. The type of lithium titanate having a spinel structure contained in the active material particles may be one type or two or more types.
[0021] Lithium titanate having a spinel structure can be, for example, of the general formula Li 4+a Ti 5 O 12 (-1≦a≦3) The subscript a in the general formula is a variable that can vary within the above range depending on the state of charge of lithium titanate.
[0022] The plurality of active material particles may further include another active material different from lithium titanate having a spinel structure.
[0023] Other active materials include, for example, lithium titanate having a ramsdellite structure (e.g., Li 2+y Ti 3 O 7 , 0≦y≦3), monoclinic titanium dioxide (TiO 2 ), anatase type titanium dioxide, rutile type titanium dioxide, hollandite type titanium composite oxide, monoclinic type niobium titanium composite oxide, and orthorhombic titanium composite oxide.
[0024] The monoclinic niobium titanium composite oxide is, for example, represented by the general formula Li x Ti 1-y M1 y Nb 2-z M2 z O 7+δ and a composite oxide represented by the general formula Li x Ti 1-y M3 y+z Nb 2-z O 7-δ Here, M1 is at least one selected from the group consisting of Zr, Si, and Sn. M2 is at least one selected from the group consisting of V, Ta, and Bi. M3 is at least one selected from Mg, Fe, Ni, Co, W, Ta, and Mo. Each subscript in the composition formula satisfies 0≦x≦5, 0≦y<1, 0≦z<2, and -0.3≦δ≦0.3.
[0025] Specific examples of monoclinic niobium titanium composite oxides include Nb 2 TiO 7 , Nb 2 Ti 2 O 9 , Nb 10 Ti 2 O 29 , Nb 14 TiO 37 and Nb 24 TiO 62 The monoclinic niobium titanium composite oxide may be a substituted niobium titanium composite oxide in which at least a part of Nb and / or Ti is substituted with a different element. Examples of the substituted element include Na, K, Ca, Co, Ni, Si, P, V, Cr, Mo, Ta, Zr, Mn, Fe, Mg, B, Pb, and Al. The substituted niobium titanium composite oxide may contain one type of substituted element, or may contain two or more types of substituted elements.
[0026] As an example of an orthorhombic titanium-containing composite oxide, Li 2+a M(I) 2-b Ti 6-c M(II) d O 14+σ Here, M(I) is at least one selected from the group consisting of Sr, Ba, Ca, Mg, Na, Cs, Rb, and K. M(II) is at least one selected from the group consisting of Zr, Sn, V, Nb, Ta, Mo, W, Y, Fe, Co, Cr, Mn, Ni, and Al. The subscripts in the composition formula are 0≦a≦6, 0≦b<2, 0≦c<6, 0≦d<6, and -0.5≦σ≦0.5. Specific examples of orthorhombic titanium-containing composite oxides include Li 2+a Na 2 Ti 6 O 14 (0≦a≦6).
[0027] The lithium titanate having a spinel structure may be present in the form of primary particles, or may be present in the form of secondary particles formed by aggregation of primary particles. At least a part of the surface of the lithium titanate having a spinel structure present in the form of particles is covered with a first binder described below. Whether the lithium titanate having a spinel structure is a secondary particle or a primary particle can be determined by observation with a scanning electron microscope (SEM: Scanning Electron Microscopy).
[0028] The average primary particle size (d50) of the lithium titanate having a spinel structure may be, for example, in the range of 0.1 μm to 30 μm, and preferably in the range of 0.7 μm to 10 μm.
[0029] The first binder is a binder that tends to easily cover the surfaces of a plurality of active material particles. In particular, the first binder is easy to cover particles made of lithium titanate having a spinel structure. According to one example, the first binder is a binder that dissolves in water and does not dissolve in an organic solvent such as NMP. In the negative electrode according to the embodiment, at least a part of the surfaces of the plurality of active material particles is covered with the first binder, so that contact between the active material particle surfaces and the electrolyte can be suppressed. This makes it possible to suppress the formation of a coating on the active material particle surfaces due to self-discharge. Therefore, it is possible to suppress an increase in the positive electrode potential, and it is possible to suppress the deterioration of the positive electrode caused by the SOC deviation and the generation of oxygen gas in the positive electrode. Since the formation of a coating on the active material particle surfaces can be suppressed, an increase in resistance in a low-temperature environment is also unlikely to occur. Therefore, according to the negative electrode according to the present embodiment, it is possible to realize excellent cycle life characteristics and low-temperature characteristics.
[0030] The first binder contains at least one selected from the group consisting of polyvinylpyrrolidone (PVP), carboxymethylcellulose (CMC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), polyvinyl chloride (PVC), polyvinyl acetate (PVAC), and polyacrylic acid. Among them, the first binder preferably contains polyvinylpyrrolidone and carboxymethylcellulose from the viewpoints of good wettability on the active material surface, high surface coverage, and a relatively small increase in cell resistance relative to the amount added.
[0031] In the active material-containing layer, the ratio of the mass of the first binder to the mass of the active material particles is within the range of 0.05% by mass to 0.50% by mass. When the active material-containing layer contains the first binder at such a ratio, the surfaces of the active material particles are covered with an appropriate amount of the first binder. If the ratio is less than 0.05% by mass, the effect of suppressing the formation of a coating due to self-discharge is poor. Therefore, it is difficult to suppress the increase in resistance due to repeated charge-discharge cycles.
[0032] As described above, the first binder tends to cover the active material particles. Therefore, when the first binder is present in an excessive amount, the active material particle surface may be excessively covered. Specifically, when the ratio is more than 0.50 mass%, the amount of the first binder covering the active material particle surface tends to be too large. When the surfaces of a plurality of active material particles are excessively covered with the first binder, not only the resistance at the beginning of the charge-discharge cycle increases, but also the resistance increase rate when the charge-discharge cycle is repeated may increase, which is not preferable.
[0033] The ratio of the mass of the first binder to the mass of the plurality of active material particles is preferably within a range of 0.10% by mass to 0.40% by mass.
[0034] The second binder is a binder different from the first binder. According to one example, the second binder is a binder that dissolves in an organic solvent such as NMP, but does not dissolve in water. The second binder is blended to fill gaps between the dispersed active material particles and to bond the active material-containing layer to the current collector. The second binder has a tendency to bond the active material particles with point contact.
[0035] The second binder may bind the active material particles together via the first binder, or may bind the active material particles together without the first binder, i.e., the second binder may be in direct contact with the surfaces of the active material particles.
[0036] The second binder contains, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyimide, and polyamide. Among them, the second binder preferably contains PVDF from the viewpoint of reducing the increase in cell resistance caused by an increase in the amount of the binder added.
[0037] In the active material-containing layer, the ratio of the mass of the second binder to the mass of the active material particles is, for example, in the range of 1.5% by mass to 30% by mass, and preferably in the range of 1.5% by mass to 5.0% by mass. If the ratio is too small, there is a disadvantage that the binding between the active material particles decreases, the AC resistance is likely to increase, and the room temperature resistance is likely to decrease. If the ratio is too large, there is a tendency for adverse effects such as increased resistance, decreased capacity, and decreased output characteristics to occur in the secondary battery.
[0038] The conductive agent is blended to improve current collection performance and reduce contact resistance between the active material and the current collector. Examples of the conductive agent include vapor grown carbon fiber (VGCF), carbon black such as acetylene black, fibrous carbon such as carbon nanotubes, and carbonaceous materials such as graphite. One of these may be used as the conductive agent, or two or more may be used in combination as the conductive agent.
[0039] The blending ratios of the multiple active material particles, the conductive agent, the first binder, and the second binder in the active material-containing layer can be changed as appropriate depending on the application of the electrode. For example, it is preferable to blend the multiple active material particles, the conductive agent, the first binder, and the second binder in ratios of 68% by mass or more and 96% by mass or less, 2% by mass or more and 30% by mass or less, 0.05% by mass or more and 0.50% by mass or less, and 1.5% by mass or more and 30% by mass or less, respectively.
[0040] The current collector is made of a material that is electrochemically stable at the potential at which lithium (Li) is inserted and removed from the active material. For example, when the active material is used as a negative electrode active material, the current collector is preferably made of copper, nickel, stainless steel, or aluminum, or an aluminum alloy containing one or more elements selected from Mg, Ti, Zn, Mn, Fe, Cu, and Si. The thickness of the current collector is preferably 5 μm or more and 20 μm or less. A current collector having such a thickness can balance the strength and weight of the electrode.
[0041] The current collector may also include a portion on the surface of which no active material-containing layer is formed, and this portion can function as a negative electrode current collecting tab.
[0042] <Measurement of binder content> A method for measuring the ratio of the mass of the first binder to the mass of the plurality of active material particles and the ratio of the mass of the second binder to the mass of the plurality of active material particles in the active material-containing layer will be described.
[0043] The active material-containing layer is removed from the secondary battery and dispersed in a sufficient amount of NMP to obtain an NMP dispersion. This dispersion causes the second binder to dissolve in the NMP dispersion. Meanwhile, the solid components contained in this dispersion (hereinafter referred to as solid component A), i.e., the active material particles, the conductive agent, and the first binder, are dispersed as solid component A. The solid component A and the solution of this dispersion are separated by a method such as filtration, and the NMP solution is collected. The mass of the second binder can be measured by evaporating and drying the NMP from the NMP solution.
[0044] Next, the solid component A obtained by the above procedure is dispersed in pure water, and the dispersion is heated. In this way, the first binder is dissolved in the pure water. Thereafter, the solid components contained in this dispersion (hereinafter referred to as solid component B), i.e., the active material particles and the conductive agent, are separated by a method such as filtration to obtain an aqueous solution. The pure water is evaporated from the aqueous solution to dryness, allowing the mass of the first binder to be measured.
[0045] Furthermore, the active material particles and the conductive agent are separated by centrifuging the solid component B. In this way, the mass of the active material particles can be measured.
[0046] <Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDX)> A method for performing element mapping on a cross section of an electrode using SEM-EDX (Scanning Electron Microscope-Energy Dispersive X-ray Spectroscopy) is described below. By performing SEM-EDX, it is possible to confirm that at least a portion of the surface of a plurality of active material particles is covered with the first binder.
[0047] First, the secondary battery is fully discharged. For example, the battery is repeatedly discharged at a current of 0.1 C in a 25°C environment until the rated end voltage or the battery voltage reaches 1.0 V, and the current value during discharge is 1 / 100 or less of the rated capacity, thereby making it possible to fully discharge the battery. Even in a discharged state, residual lithium ions may remain.
[0048] A secondary battery containing an electrode in a fully discharged state (State of Charge: 0%) is disassembled in a glove box filled with argon. The electrode to be measured is removed from the disassembled secondary battery. The electrode is washed with an appropriate solvent. For example, ethyl methyl carbonate is used as a solvent for washing. If the washing is insufficient, it may be difficult to observe the particles due to the influence of lithium carbonate or lithium fluoride remaining in the electrode. The target electrode thus removed is cut with an ion milling device. When cutting the electrode, the electrode is cut along the thickness direction. The cross section of the electrode after cutting is attached to an SEM sample stage. At this time, a conductive tape or the like is used to treat the electrode so that it does not peel off or float from the sample stage. The electrode (active material-containing layer) attached to the SEM sample stage is observed with an SEM to obtain an SEM image. The SEM measurement is performed at a magnification of 10,000 times. It is also preferable to maintain an inert atmosphere when introducing the electrode into the sample chamber.
[0049] Furthermore, an element mapping image corresponding to the SEM image is obtained by EDX. By considering the SEM image and the element mapping image in combination, it is possible to confirm that at least a portion of the surface of the plurality of active material particles is covered with the first binder.
[0050] The crystal structure and elemental composition of the negative electrode active material can be confirmed by, for example, powder X-ray diffraction (XRD) measurement and inductively coupled plasma (ICP) emission spectroscopy, which will be described below.
[0051] <Powder X-ray diffraction measurement of active materials> The powder X-ray diffraction measurement of the active material can be carried out, for example, as follows. First, the target sample is crushed until the average particle size is about 5 μm. The crushed sample is filled into the holder portion formed on the glass sample plate, with a depth of 0.2 mm. At this time, care is taken to ensure that the sample is filled sufficiently into the holder portion. Also, care is taken to fill the sample with just the right amount so that cracks, voids, etc. do not occur. Next, another glass plate is pressed from the outside to flatten the surface of the sample filled into the holder portion. Care is taken to ensure that the amount of filling is not too much or too little, resulting in unevenness compared to the reference surface of the holder.
[0052] Next, the glass plate filled with the sample is placed in a powder X-ray diffractometer, and a diffraction pattern (XRD pattern; X-Ray Diffraction pattern) is obtained using Cu-Kα radiation.
[0053] In addition, the orientation of the particles may become large depending on the particle shape of the sample. When the orientation of the sample is high, the peak position may shift or the intensity ratio may change depending on how the sample is filled. Samples with extremely high orientation are measured using a glass capillary. Specifically, the sample is inserted into a capillary, and the capillary is placed on a rotating sample stage for measurement. This measurement method can reduce the orientation. As the glass capillary, it is preferable to use a Lindemann glass capillary with a diameter of 1 mm to 6 mmφ.
[0054] When performing powder X-ray diffraction measurement on the active material contained in a secondary battery or electrode, it can be performed, for example, as follows. First, in order to grasp the crystalline state of the active material, the active material is placed in a state in which lithium ions are completely removed. For example, when the active material is used in a negative electrode, the battery is placed in a completely discharged state. For example, the battery is discharged at a current of 0.1 C in a 25° C. environment until the rated end voltage or the battery voltage reaches 1.0 V, and the current value during discharge is set to 1 / 100 or less of the rated capacity, thereby placing the battery in a discharged state. Residual lithium ions may still be present even in the discharged state.
[0055] Next, disassemble the battery in a glove box filled with argon, take out the electrodes, and wash them with a suitable solvent. As a suitable solvent, for example, ethyl methyl carbonate can be used. If the cleaning of the electrodes is insufficient, impurity phases such as lithium carbonate and lithium fluoride may be mixed in due to the influence of lithium ions remaining in the electrodes. In that case, it is advisable to use an airtight container in which the measurement atmosphere can be carried out in an inert gas. At this time, measure and grasp in advance the peaks derived from the metal foil as the current collector, the conductive agent, the binder, etc. using EDX. Of course, if these can be grasped in advance, this operation can be omitted. When the peak of the current collector overlaps with the peak of the active material, it is desirable to peel off the active material-containing layer from the current collector for measurement. This is for separating the overlapping peaks when quantitatively measuring the peak intensity. The active material-containing layer may be physically peeled off. The active material-containing layer is easily peeled off when ultrasonic waves are applied in a suitable solvent. When ultrasonic treatment is performed to peel off the active material-containing layer from the current collector, the electrode body powder (including the active material, the conductive agent, and the binder) can be recovered by volatilizing the solvent. By filling the recovered electrode body powder into, for example, a capillary made of Lindemann glass and measuring it, powder X-ray diffraction measurement of the active material can be performed. Note that the electrode body powder recovered by ultrasonic treatment can also be used for various analyses other than powder X-ray diffraction measurement.
[0056] <Inductively Coupled Plasma Emission Spectrometry> The composition of the active material can be analyzed, for example, using inductively coupled plasma (ICP) emission spectrometry. At this time, the abundance ratio (molar ratio) of each element depends on the sensitivity of the analytical device used. Therefore, the measured molar ratio may deviate in numerical value from the actual molar ratio by the error of the measuring device. However, even if the numerical value deviates within the error range of the analytical device, the performance of the active material according to the embodiment can be sufficiently exhibited.
[0057] To measure the composition of the active material incorporated in the battery by ICP emission spectrometry, specifically, it is performed according to the following procedure.
[0058] First, the electrode containing the active material to be measured is removed from the secondary battery and washed according to the procedure described in the section on powder X-ray diffraction measurement. The part containing the electrode active material, such as the active material-containing layer, is peeled off from the washed electrode. For example, the part containing the electrode active material can be peeled off by irradiating it with ultrasonic waves. As a specific example, the electrode can be placed in ethyl methyl carbonate in a glass beaker and vibrated in an ultrasonic cleaner to peel off the active material-containing layer containing the electrode active material from the electrode current collector.
[0059] Next, the peeled off part is heated in air for a short period of time (for example, at 500°C for about an hour) to burn off unnecessary components such as binder components and carbon. This residue is dissolved in acid to create a liquid sample containing the active material. The acid that can be used in this case is hydrochloric acid, nitric acid, sulfuric acid, hydrogen fluoride, etc. This liquid sample can be subjected to ICP analysis to determine the composition of the active material.
[0060] <Method for manufacturing a negative electrode according to the first embodiment> The negative electrode according to the first embodiment can be produced, for example, by the following method.
[0061] First, active material particles containing lithium titanate having a spinel structure, a conductive agent, and a second binder are suspended in a suitable solvent to prepare a slurry. At this time, a first binder is further added to the slurry. The first binder is added to the slurry in the form of, for example, an ethanol solution. The solid content concentration in the obtained slurry is, for example, within a range of 40% by mass to 65% by mass. The mixing ratio of the active material particles, the conductive agent, the first binder, and the second binder is the ratio described above.
[0062] The prepared slurry is applied to a current collector such as an aluminum foil with a desired basis weight using a coating machine, and the coating is dried. For example, vacuum drying at 120°C for 48 hours is preferably performed to dry the coating. In this way, a member having a current collector and an active material-containing layer formed on the current collector is prepared. The obtained member is, for example, in a strip shape. The member is pressed to a predetermined electrode density. In this way, the negative electrode according to the first embodiment can be prepared.
[0063] The negative electrode according to this embodiment may be produced by the following method.
[0064] First, active material particles containing lithium titanate having a spinel structure, a conductive agent, and a second binder are suspended in a suitable solvent to prepare a slurry. Using this slurry, coating, drying, and pressing are performed in the same manner as in the above-mentioned manufacturing method to obtain an electrode structure not containing the first binder. Then, this electrode structure is immersed in an ethanol solution containing the first binder (first binder-containing solution). The immersion process is preferably performed by immersing the electrode structure at room temperature for 30 seconds or more and 120 seconds or less.
[0065] Thereafter, the electrode structure is pulled out of the first binder-containing solution, and excess solution adhering to the member is wiped off. The electrode structure is then dried. For example, the electrode structure is preferably dried on a hot plate set at 120°C, and then dried for 48 hours or more in a vacuum dryer set at 120°C. In this way, at least a portion of the surface of the plurality of active material particles can be coated with the first binder.
[0066] According to the first embodiment described above, a negative electrode is provided. The negative electrode includes a current collector and an active material-containing layer supported on at least a part of the current collector. The active material-containing layer includes a plurality of active material particles, a first binder that covers at least a part of the surface of the plurality of active material particles, and a second binder different from the first binder. The plurality of active material particles include lithium titanate having a spinel structure. The first binder includes at least one selected from the group consisting of polyvinylpyrrolidone, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, polyvinyl chloride, polyvinyl acetate, and polyacrylic acid. The ratio of the mass of the first binder to the mass of the plurality of active material particles is within a range of 0.05% by mass to 0.50% by mass.
[0067] Since at least a part of the surface of the active material particles is coated with the first binder, the formation of a coating on the surface of the active material particles due to self-discharge can be suppressed. Therefore, the increase in the positive electrode potential due to the charge-discharge cycle can be suppressed, and the deterioration of the positive electrode due to the SOC deviation and the generation of oxygen gas in the positive electrode can be suppressed. Therefore, the negative electrode according to this embodiment can achieve excellent cycle life characteristics and low-temperature characteristics.
[0068] Second embodiment According to a second embodiment, a negative electrode is provided. The negative electrode includes a current collector and an active material-containing layer supported on at least a part of the current collector. The active material-containing layer includes a plurality of active material particles, a first binder that covers a part of the surface of the plurality of active material particles, a second binder different from the first binder, and an aluminum-containing coating that covers another part of the surface of the plurality of active material particles. The plurality of active material particles include lithium titanate having a spinel structure. The first binder includes at least one selected from the group consisting of polyvinylpyrrolidone, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, polyvinyl chloride, polyvinyl acetate, and polyacrylic acid. The ratio of the mass of the first binder to the mass of the plurality of active material particles is within a range of 0.01% by mass to 0.50% by mass. The ratio of the mass of aluminum contained in the aluminum-containing coating to the mass of the plurality of active material particles is within a range of 0.04% by mass to 0.30% by mass.
[0069] The negative electrode according to the second embodiment has a similar configuration to the negative electrode according to the first embodiment, except that the surfaces of the plurality of active material particles are coated with an aluminum-containing coating together with the first binder. In the negative electrode according to the second embodiment, a mixture of the first binder and the aluminum-containing coating may coat at least a portion of the surfaces of the plurality of active material particles.
[0070] The aluminum-containing coating exhibits the same effect as the first binder described above. That is, the aluminum-containing coating suppresses contact between the active material particle surface and the electrolyte, so that the formation of a coating on the active material particle surface due to self-discharge can be suppressed, and the increase in cell resistance, particularly the increase in low-temperature resistance, due to cell use can be suppressed. Therefore, the increase in positive electrode potential due to charge / discharge cycles can be suppressed, and the deterioration of the positive electrode due to SOC deviation and the generation of oxygen gas in the positive electrode can be suppressed.
[0071] The active material particles, the first binder, and the second binder contained in the negative electrode according to the second embodiment may be the same as those described in the first embodiment. However, since the negative electrode according to the second embodiment has an aluminum-containing coating on the surface of the active material particles, the content of the first binder can be reduced accordingly.
[0072] Specifically, the ratio of the mass of the first binder to the mass of the plurality of active material particles is, for example, in the range of 0.01 mass % to 0.50 mass %, and preferably in the range of 0.03 mass % to 0.20 mass %.
[0073] The active material-containing layer includes an aluminum-containing coating that covers a portion of the active material particles. The aluminum-containing coating contains an aluminum (Al) component. The aluminum-containing coating has a chemical structure that is not clear, but has a structure in which an organic substituent is bonded or coordinated to an aluminum atom. As described below, the aluminum-containing coating is a coating that is produced using an organoaluminum compound as an aluminum source. As the organoaluminum compound, for example, at least one selected from the group consisting of aluminum alkoxides and aluminum chelates (complexes) can be mentioned. As the organic substituent, for example, at least one selected from the group consisting of the substituents of aluminum alkoxides and aluminum chelates shown below can be mentioned.
[0074] Examples of aluminum alkoxides include di-2-butoxyaluminum ethyl acetoacetate (Al(C 4 H 9 O) 2 (C 6 H 9 O 3 )), aluminum tri-2-butoxide (Al(OC 4 H 9 ) 3 ), di-2-butoxyaluminum acetylacetate (Al(C 4 H 9 O) 2 (C5 H 7 O 2 )), Aluminum sec-butoxide (Al(O-sec-C 4 H 9 ) 3 ) and the like can be used. As the aluminum chelate, for example, aluminum trisacetylacetate (Al(C 5 H 7 O 2 ) 3 ), Aluminum bisethylacetoacetate monoacetylacetate (Al(C 5 H 7 O 2 )(C 6 H 9 O 3 ) 2 ), Aluminum trisethylacetoacetate (Al(C 6 H 9 O 3 ) 3 These may be used alone or in combination of two or more.
[0075] The first binder and the aluminum-containing coating that coexist on the surfaces of the active material particles may or may not be chemically bonded to each other. For example, a methoxy group may be bonded to the aluminum atom or an acetyl group may be coordinated to the aluminum atom.
[0076] In the active material-containing layer, the ratio of the mass of aluminum contained in the aluminum-containing coating to the mass of the multiple active material particles is within the range of 0.04% by mass to 0.30% by mass. If the ratio is less than 0.04% by mass, the effect of suppressing the formation of a coating due to self-discharge may be poor. Therefore, it may be difficult to suppress the increase in resistance due to repeated charge-discharge cycles. If the ratio exceeds 0.30% by mass, there is a risk of an increase in resistance due to the large amount of aluminum-containing coating coating the surfaces of the active material particles. The ratio is preferably within the range of 0.06% by mass to 0.25% by mass.
[0077] The blending ratios of the multiple active material particles, conductive agent, first binder, second binder, and aluminum-containing coating in the active material-containing layer can be changed as appropriate depending on the use of the electrode. For example, it is preferable to blend the multiple active material particles, conductive agent, first binder, second binder, and aluminum-containing coating in ratios of 68 mass% or more and 96 mass% or less, 2 mass% or more and 30 mass% or less, 0.01 mass% or more and 0.50 mass% or less, 1.5 mass% or more and 30 mass% or less, and 0.04 mass% or more and 0.30 mass% or more, respectively.
[0078] <Inductively coupled plasma optical emission spectroscopy> The aluminum content in the active material can be calculated by analysis using inductively coupled plasma atomic emission spectrometry (ICP-AES).
[0079] Specifically, the active material-containing layer to be measured is peeled off from the electrode current collector with an aqueous solvent or NMP, and a dispersion liquid in which the electrode components are dispersed in the solvent is prepared. The solid components are extracted and recovered from this dispersion liquid. The solid components are dissolved in an acidic aqueous solution by using an acid decomposition method or an alkali melting method, etc., to obtain a melt. In the acid decomposition method, an appropriate acid and the solid components are placed in a pressure vessel and heated to dissolve the solid components in the acid. In this way, a sample solution containing the electrode components is obtained. The electrode components may mainly include metal components that constitute the active material-containing layer.
[0080] The sample solution is quantitatively analyzed by ICP analysis. The composition of the active material is determined from the analysis results. The aluminum content in the active material is calculated from the analysis values of at least one of the active material components, such as Ti and Al, and the active material composition.
[0081] Various measurements, except for the aluminum content, can be carried out in the same manner as described in the first embodiment.
[0082] <Method for manufacturing a negative electrode according to the second embodiment> The negative electrode according to the second embodiment can be produced, for example, by the following method.
[0083] First, an active material particle containing lithium titanate having a spinel structure, a conductive agent, and a second binder are suspended in a suitable solvent to prepare a slurry. At this time, a first binder and an organoaluminum compound are further added to the slurry. The first binder and the organoaluminum compound are prepared in the form of a solution diluted with, for example, ethanol or NMP. Although there is no particular limitation on the mixing method, it is preferable to add an aluminum-containing diluent to the slurry and then add a diluent containing the first binder component, since this allows efficient coating of the negative electrode active material.
[0084] The active material particles, conductive agent, first binder, second binder and organoaluminum compound are mixed in the above-mentioned proportions. The solid content of the resulting slurry is, for example, in the range of 40% by mass to 65% by mass.
[0085] The prepared slurry is applied to a current collector such as an aluminum foil with a desired basis weight using a coating machine, and the coating is dried. For example, vacuum drying at 120°C for 48 hours is preferably performed to dry the coating. In this way, a member having a current collector and an active material-containing layer formed on the current collector is prepared. The obtained member is, for example, in a strip shape. The member is pressed to a predetermined electrode density. In this way, the negative electrode according to the second embodiment can be prepared.
[0086] The negative electrode according to this embodiment may be produced by the following method.
[0087] First, active material particles containing lithium titanate having a spinel structure, a conductive agent, and a second binder are suspended in a suitable solvent to prepare a slurry. Using this slurry, coating, drying, and pressing are performed in the same manner as in the above-mentioned manufacturing method to obtain an electrode structure. This electrode structure does not contain a first binder and an aluminum-containing coating. Next, this electrode structure is impregnated with an ethanol solution or NMP solution containing the first binder and an organoaluminum compound. Then, the obtained electrode structure is subjected to a drying process, so that a part of the surface of the plurality of active material particles is coated with the first binder, and another part of the surface of the plurality of active material particles is coated with the aluminum-containing coating. Here, too, the order of coating is not particularly limited. It is desirable to first form a coating (including impregnation and drying) with a dilute solution containing an aluminum compound, and then form a coating again with a dilute solution containing the first binder. The reason is that the coating after coating with the dilute solution of the aluminum compound is insoluble in a solvent such as ethanol, whereas the first binder dissolves again in the solvent when it comes into contact with a soluble solvent after coating, making it difficult to control the amount of coating.
[0088] The drying is preferably carried out, for example, on a hot plate set at 120° C., and then in a vacuum dryer set at 120° C. for 48 hours or more.
[0089] Although ethanol is exemplified as a solvent used for diluting the first binder and the organoaluminum compound, the dilution liquid is not limited to ethanol. The dilution liquid is preferably a solvent with a relatively low boiling point that does not remain in the electrode after drying and is unlikely to react with the metal alkoxide or the electrode components. By using a dilution solvent that does not remain in the electrode, it is possible to prevent the efficiency from decreasing due to the remaining solvent during charging and discharging of the battery. In order not to react with the metal alkoxide or the electrode components, a solvent with a low water content is preferable. In consideration of safety, cost, and ease of handling, ethanol can be preferably used. Methanol can be mentioned as another example, but it is toxic and should be handled with care.
[0090] According to the second embodiment described above, a negative electrode is provided. The negative electrode includes a current collector and an active material-containing layer supported on at least a part of the current collector. The active material-containing layer includes a plurality of active material particles, a first binder that covers a part of the surface of the plurality of active material particles, a second binder different from the first binder, and an aluminum-containing coating that covers another part of the surface of the plurality of active material particles. The plurality of active material particles include lithium titanate having a spinel structure. The first binder includes at least one selected from the group consisting of polyvinylpyrrolidone, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, polyvinyl chloride, polyvinyl acetate, and polyacrylic acid. The ratio of the mass of the first binder to the mass of the plurality of active material particles is within a range of 0.01% by mass to 0.50% by mass. The ratio of the mass of aluminum contained in the aluminum-containing coating to the mass of the plurality of active material particles is within a range of 0.04% by mass to 0.30% by mass.
[0091] In the negative electrode according to the second embodiment, the surfaces of the active material particles are coated with the first binder and the aluminum-containing coating, so that the formation of a coating on the active material particle surface due to self-discharge can be suppressed. Therefore, the increase in the positive electrode potential due to the charge-discharge cycle can be suppressed, and the deterioration of the positive electrode due to the SOC deviation and the generation of oxygen gas in the positive electrode can be suppressed. Therefore, the negative electrode according to this embodiment can realize excellent cycle life characteristics and low-temperature characteristics.
[0092] Third embodiment According to a third embodiment, a secondary battery is provided that includes the negative electrode according to the first or second embodiment, a positive electrode, and an electrolyte. The secondary battery may be, for example, a lithium ion secondary battery. The secondary battery may be a non-aqueous electrolyte secondary battery that includes a non-aqueous electrolyte.
[0093] The secondary battery may further include a separator disposed between the positive electrode and the negative electrode. The negative electrode, the positive electrode, and the separator may constitute an electrode group. The electrolyte may be held in the electrode group.
[0094] Moreover, the secondary battery may further include an exterior member that contains the electrode group and the electrolyte.
[0095] Furthermore, the secondary battery may further include a negative electrode terminal electrically connected to the negative electrode and a positive electrode terminal electrically connected to the positive electrode.
[0096] The negative electrode, the positive electrode, the electrolyte, the separator, the exterior member, the negative electrode terminal, and the positive electrode terminal will be described in detail below.
[0097] (1) Negative electrode As the negative electrode included in the secondary battery according to the third embodiment, the negative electrode according to the first or second embodiment can be used.
[0098] The density of the negative electrode active material-containing layer (excluding the current collector) is 1.8 g / cm 3 More than 2.8g / cm 3 A negative electrode having a density of the negative electrode active material-containing layer within this range is excellent in energy density and electrolyte retention. The density of the negative electrode active material-containing layer is preferably 2.1 g / cm or less. 3 More than 2.6g / cm 3 It is more preferable that:
[0099] (2) Positive electrode The positive electrode may include a positive electrode current collector and a positive electrode active material-containing layer. The positive electrode active material-containing layer may be formed on one or both sides of the positive electrode current collector. The positive electrode active material-containing layer may include a positive electrode active material, and optionally a conductive agent and a binder.
[0100] As the positive electrode active material, for example, an oxide or a sulfide can be used. The positive electrode may contain one type of compound alone as the positive electrode active material, or may contain two or more types of compounds in combination. Examples of oxides and sulfides include compounds that can insert and remove Li or Li ions.
[0101] Such compounds include, for example, manganese dioxide (MnO 2) Iron oxide, copper oxide, nickel oxide, lithium manganese composite oxide (e.g., Li x Mn 2 O 4 Or Li x MnO 2 ; 0 < x ≤ 1), lithium nickel composite oxide (e.g., Li x NiO 2 ; 0 < x ≤ 1), lithium cobalt composite oxide (e.g., Li x CoO 2 ; 0 < x ≤ 1), lithium nickel cobalt composite oxide (e.g., Li x Ni 1-y Co y O 2 ; 0 < x ≤ 1, 0 < y < 1), lithium manganese cobalt composite oxide (e.g., Li x Mn y Co 1-y O 2 ; 0 < x ≤ 1, 0 < y < 1), lithium manganese nickel composite oxide having a spinel structure (e.g., Li x Mn 2-y Ni y O 4 ; 0 < x ≤ 1, 0 < y < 2), lithium phosphate having an olivine structure (e.g., Li x FePO 4 ; 0 < x ≤ 1, Li x Fe 1-y Mn y PO 4 ; 0 < x ≤ 1, 0 < y < 1, Li x CoPO 4 ; 0 < x ≤ 1), iron sulfate (Fe 2 (SO 4 ) 3 ) vanadium oxide (e.g., V 2 O 5 ), and lithium nickel cobalt manganese composite oxide (Li x Ni 1-y-z Co y Mn z O 2 ; 0 < x ≤ 1, 0 < y < 1, 0 < z < 1, y + z < 1) are included.
[0102] Among the above, examples of more preferable compounds as the positive electrode active material include lithium manganese composite oxides having a spinel structure (for example, Li x Mn 2 O 4 ; 0 < x ≦ 1), lithium nickel composite oxides (for example, Li x NiO 2 ; 0 < x ≦ 1), lithium cobalt composite oxides (for example, Li x CoO 2 ; 0 < x ≦ 1), lithium nickel cobalt composite oxides (for example, Li x Ni 1-y Co y O 2 ; 0 < x ≦ 1, 0 < y < 1), lithium manganese nickel composite oxides having a spinel structure (for example, Li x Mn 2-y Ni y O 4 ; 0 < x ≦ 1, 0 < y < 2), lithium manganese cobalt composite oxides (for example, Li x Mn y Co 1-y O 2 ; 0 < x ≦ 1, 0 < y < 1), lithium iron phosphate (for example, Li x FePO 4 ; 0 < x ≦ 1), and lithium nickel cobalt manganese composite oxides (Li x Ni 1-y-z Co y Mn z O 2 ; 0 < x ≦ 1, 0 < y < 1, 0 < z < 1, y + z < 1) are included. When these compounds are used as the positive electrode active material, the positive electrode potential can be increased.
[0103] When a room temperature molten salt is used as the electrolyte of the battery, it is preferable to use a positive electrode active material containing lithium iron phosphate, Li x VPO 4 F (0 ≦ x ≦ 1), a lithium manganese composite oxide, a lithium nickel composite oxide, a lithium nickel cobalt composite oxide, or a mixture thereof. Since these compounds have low reactivity with the room temperature molten salt, the cycle life can be improved. Details of the room temperature molten salt will be described later.
[0104] The primary particle size of the positive electrode active material is preferably 100 nm or more and 1 μm or less. A positive electrode active material with a primary particle size of 100 nm or more is easy to handle in industrial production. A positive electrode active material with a primary particle size of 1 μm or less can smoothly diffuse lithium ions in the solid.
[0105] The specific surface area of the positive electrode active material is 0.1 m 2 / g or more 10m 2 / g or less. 2 A positive electrode active material having a specific surface area of 10m / g or more can secure sufficient sites for absorbing and releasing Li ions. 2 A positive electrode active material having a specific surface area of 100 / g or less is easy to handle in industrial production and can ensure good charge-discharge cycle performance.
[0106] The binder is blended to fill the gaps between the dispersed positive electrode active material and to bind the positive electrode active material and the positive electrode current collector. Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-based rubber, polyacrylic acid compounds, imide compounds, carboxy methyl cellulose (CMC), and salts of CMC. One of these may be used as the binder, or two or more may be used in combination as the binder.
[0107] The conductive agent is blended to improve current collection performance and reduce contact resistance between the positive electrode active material and the positive electrode current collector. Examples of the conductive agent include vapor grown carbon fiber (VGCF), carbon black such as acetylene black, graphite, carbon nanofiber, and carbon nanotube, and other carbonaceous materials. One of these may be used as the conductive agent, or two or more may be combined and used as the conductive agent. The conductive agent may also be omitted.
[0108] In the positive electrode active material-containing layer, the positive electrode active material and the binder are preferably mixed in an amount of 80% by mass to 98% by mass and 2% by mass to 20% by mass, respectively.
[0109] By making the amount of binder 2% by mass or more, sufficient electrode strength can be obtained. In addition, the binder can function as an insulator. Therefore, by making the amount of binder 20% by mass or less, the amount of insulator contained in the electrode is reduced, and the internal resistance can be reduced.
[0110] When a conductive agent is added, the positive electrode active material, the binder, and the conductive agent are preferably mixed in proportions of 77% by mass or more and 95% by mass or less, 2% by mass or more and 20% by mass or less, and 3% by mass or more and 15% by mass or less, respectively.
[0111] By making the amount of the conductive agent 3% by mass or more, the above-mentioned effects can be achieved. Also, by making the amount of the conductive agent 15% by mass or less, the ratio of the conductive agent in contact with the electrolyte can be reduced. If this ratio is low, decomposition of the electrolyte during high-temperature storage can be reduced.
[0112] The positive electrode current collector is preferably an aluminum foil or an aluminum alloy foil containing one or more elements selected from Mg, Ti, Zn, Ni, Cr, Mn, Fe, Cu, and Si.
[0113] The thickness of the aluminum foil or aluminum alloy foil is preferably 5 μm or more and 20 μm or less, more preferably 15 μm or less. The purity of the aluminum foil is preferably 99 mass% or more. The content of transition metals such as iron, copper, nickel, and chromium contained in the aluminum foil or aluminum alloy foil is preferably 1 mass% or less.
[0114] The positive electrode current collector may also include a portion on the surface of which the positive electrode active material-containing layer is not formed, and this portion can function as a positive electrode current collecting tab.
[0115] The positive electrode can be produced, for example, by the following method. First, an active material, a conductive agent, and a binder are suspended in a solvent to prepare a slurry. This slurry is applied to one or both sides of a current collector. Next, the applied slurry is dried to obtain a laminate of an active material-containing layer and a current collector. Then, this laminate is pressed. In this manner, a positive electrode is produced.
[0116] Alternatively, the positive electrode may be prepared by the following method: first, the active material, the conductive agent, and the binder are mixed to obtain a mixture, then the mixture is formed into pellets, and then the pellets are placed on a current collector to obtain a positive electrode.
[0117] (3) Electrolyte The electrolyte may be, for example, a liquid nonaqueous electrolyte or a gel nonaqueous electrolyte. The liquid nonaqueous electrolyte is prepared by dissolving an electrolyte salt as a solute in an organic solvent. The concentration of the electrolyte salt is preferably 0.5 mol / L or more and 2.5 mol / L or less.
[0118] Examples of electrolyte salts include lithium perchlorate (LiClO 4 ), lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium arsenic hexafluoride (LiAsF 6 ), lithium trifluoromethanesulfonate (LiCF 3 SO 3 ), and lithium bistrifluoromethylsulfonylimide (LiN(CF 3 SO 2 ) 2 The electrolyte salt is preferably one that is not easily oxidized even at high potential, such as LiPF 6 is most preferred.
[0119] Examples of organic solvents include cyclic carbonates such as propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC); chain carbonates such as diethyl carbonate (DEC), dimethyl carbonate (DMC), and methyl ethyl carbonate (MEC); cyclic ethers such as tetrahydrofuran (THF), 2-methyl tetrahydrofuran (2MeTHF), and dioxolane (DOX); chain ethers such as dimethoxyethane (DME) and diethoxyethane (DEE); γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane (SL). These organic solvents can be used alone or as a mixed solvent.
[0120] The gelled non-aqueous electrolyte is prepared by compounding a liquid non-aqueous electrolyte with a polymeric material. As the polymeric material, for example, at least one selected from the group consisting of polyvinylidene fluoride, polyacrylonitrile, polyethylene oxide, acrylic polymer, polyamide, and polyvinyl alcohol can be used. By using a gelled electrolyte as the electrolyte, it is possible to suppress the elution of metal from the positive electrode and the generation of gas such as hydrogen. As a result, excellent cycle life characteristics can be obtained.
[0121] Alternatively, as the nonaqueous electrolyte, in addition to liquid nonaqueous electrolytes and gel nonaqueous electrolytes, room temperature molten salts containing lithium ions (ionic melts), polymer solid electrolytes, inorganic solid electrolytes, and the like may be used.
[0122] Room temperature molten salts (ionic melts) refer to organic salts consisting of a combination of organic cations and anions that can exist as a liquid at room temperature (15°C or higher and 25°C or lower). Room temperature molten salts include room temperature molten salts that exist as a liquid by themselves, room temperature molten salts that become liquid when mixed with an electrolyte salt, room temperature molten salts that become liquid when dissolved in an organic solvent, and mixtures of these. In general, the melting point of room temperature molten salts used in secondary batteries is 25°C or lower. In addition, organic cations generally have a quaternary ammonium skeleton.
[0123] The polymer solid electrolyte is prepared by dissolving an electrolyte salt in a polymer material and solidifying it.
[0124] The inorganic solid electrolyte is a solid material that has Li-ion conductivity.
[0125] (4) Separator The separator is formed, for example, from a porous film containing polyethylene (PE), polypropylene (PP), cellulose, or polyvinylidene fluoride (PVdF), or a synthetic resin nonwoven fabric. From the viewpoint of safety, it is preferable to use a porous film formed from polyethylene or polypropylene. This is because these porous films melt at a certain temperature and are capable of cutting off electric current.
[0126] A solid electrolyte layer containing solid electrolyte particles can also be used as the separator. The solid electrolyte layer may contain one type of solid electrolyte particles or may contain multiple types of solid electrolyte particles. The solid electrolyte layer may be a solid electrolyte composite membrane containing solid electrolyte particles. The solid electrolyte composite membrane is, for example, a membrane formed from solid electrolyte particles using a polymer material. The solid electrolyte layer may contain at least one selected from the group consisting of a plasticizer and an electrolyte salt. When the solid electrolyte layer contains an electrolyte salt, for example, the alkali metal ion conductivity of the solid electrolyte layer can be further increased.
[0127] Examples of the polymeric material include polyethers, polyesters, polyamines, polyethylenes, silicones, and polysulfides.
[0128] The lithium ion conductivity of the solid electrolyte is 1×10 at 25°C. -10 It is preferable that the lithium ion conductivity of the solid electrolyte at 25° C. is 1×10 -10 By having a lithium ion conductivity of 1×10 S / cm or more, the lithium ion concentration near the surface of the solid electrolyte is likely to be high, which can improve the rate performance and life characteristics. The lithium ion conductivity of the solid electrolyte at 25°C is 1×10 -6 The upper limit of the lithium ion conductivity of the solid electrolyte is, for example, 2×10 -2 S / cm.
[0129] Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and polymer solid electrolytes. Specifically, the solid electrolyte is a sulfide-based Li 2 SEP 2 S 5 Lithium lanthanum titanium composite oxide (Li 0.5 La 0.5 TiO 3 ), inorganic compounds with LISICON-type structures (e.g., Li 3.6 S 0.6 P 0.4 O 4 ), an inorganic compound with a NASICON structure, and amorphous LIPON(Li 2.9 PO 3.3 N 0.46 ), lithium calcium zirconium oxide (Li 1.2 Zr 1.9 Ca 0.1 (PO 4 ) 3) and inorganic compounds having a garnet structure. The coating layer may contain one type of solid electrolyte or may contain two or more types of solid electrolytes.
[0130] Inorganic compounds having a NASICON skeleton include those having the general formula LiM 2 (PO 4 ) 3 (M is at least one selected from Ti, Ge, Sr, Zr, Sn and Al). 1+x Al x Ge 2-x (PO 4 ) 3 , Li 1+x Al x Zr 2-x (PO 4 ) 3 , Li 1+x Al x Ti 2-x (PO 4 ) 3 (LATP) is preferred because it has high ionic conductivity and high electrochemical stability against water. In the above, x preferably satisfies 0≦x≦0.5.
[0131] Examples of inorganic compounds having a garnet structure include Li 5+x A y La 3-y M 2 O 12 (A is at least one selected from the group consisting of Ca, Sr and Ba, and M is at least one selected from the group consisting of Nb and Ta), Li 3 M 2-x Zr 2 O 12 (M is at least one selected from the group consisting of Ta and Nb), Li 7-3x Al x La 3 Zr 3 O 12 , and Li 7 La 3 Zr 2 O 12In the above, x is, for example, 0≦x<0.8, and preferably 0≦x≦0.5. y is, for example, 0≦y<2. The oxide having a garnet structure may be composed of one of these compounds, or may contain a mixture of two or more of these compounds. Among these, Li 6.25 Al 0.25 La 3 Zr 3 O 12 and Li 7 La 3 Zr 2 O 12 Since it has high ionic conductivity and is electrochemically stable, it has excellent discharge performance and cycle life performance.
[0132] It is not preferable for the solid electrolyte to contain elemental sulfur, since the sulfur component dissolves in the organic electrolyte described below.It is preferable for the solid electrolyte to not contain elemental sulfur.
[0133] A preferred solid electrolyte is LATP (Li 1+x Al x Ti 2-x (PO 4 ) 3 ), amorphous LIPON, garnet-type lithium lanthanum zirconium oxides (e.g., Li 7 La 3 Zr 2 O 12 :LLZ) and other oxides.
[0134] LiM with NASICON-type framework 2 (PO 4 ) 3 The lithium ion conductivity of the inorganic compound represented by the formula (I) at 25°C is, for example, 1×10 -3 S / cm~1×10 -5 S / cm range. 2.9 PO 3.3 N 0.46 ) at 25°C has a lithium ion conductivity of 3×10 -6 S / cm. Garnet-type LLZ (Li 7 La3 Zr 2 O 12 ) at 25°C has a lithium ion conductivity of 3×10 -4 S / cm.
[0135] Among these, the solid electrolyte is preferably LATP having a NASICON-type skeleton. LATP has high lithium ion conductivity and is not decomposed by water, so it can exist stably even in air.
[0136] (5) Exterior materials As the exterior member, for example, a container made of a laminate film or a metal container can be used.
[0137] The thickness of the laminate film is, for example, 0.5 mm or less, preferably 0.2 mm or less.
[0138] The laminate film is a multi-layer film including a plurality of resin layers and a metal layer interposed between the resin layers. The resin layers include polymeric materials such as polypropylene (PP), polyethylene (PE), nylon, and polyethylene terephthalate (PET). The metal layer is preferably made of aluminum foil or aluminum alloy foil for weight reduction. The laminate film can be molded into the shape of the exterior member by sealing it by heat fusion.
[0139] The thickness of the wall of the metal container is, for example, 1 mm or less, more preferably 0.5 mm or less, and even more preferably 0.2 mm or less.
[0140] The metal container is made of, for example, aluminum or an aluminum alloy. The aluminum alloy preferably contains elements such as magnesium, zinc, and silicon. When the aluminum alloy contains transition metals such as iron, copper, nickel, and chromium, the content of the transition metals is preferably 100 ppm by mass or less.
[0141] The shape of the exterior member is not particularly limited. The shape of the exterior member may be, for example, flat (thin), rectangular, cylindrical, coin, or button. The exterior member can be appropriately selected depending on the battery dimensions and the application of the battery.
[0142] (6) Negative terminal The negative electrode terminal can be made of a material that is electrochemically stable at the Li absorption / release potential of the negative electrode active material and has electrical conductivity. Specifically, the material of the negative electrode terminal can be copper, nickel, stainless steel, aluminum, or an aluminum alloy containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si. The material of the negative electrode terminal is preferably aluminum or an aluminum alloy. The negative electrode terminal is preferably made of the same material as the negative electrode current collector in order to reduce the contact resistance with the negative electrode current collector.
[0143] (7) Positive terminal The positive electrode terminal has a potential range of 3V to 5V with respect to the redox potential of lithium (vs. Li / Li + ) and can be formed from a material that is electrically stable and conductive. Examples of the material for the positive electrode terminal include aluminum and an aluminum alloy containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si. The positive electrode terminal is preferably formed from the same material as the positive electrode current collector in order to reduce the contact resistance with the positive electrode current collector.
[0144] Next, the secondary battery according to the third embodiment will be described more specifically with reference to the drawings.
[0145] Fig. 1 is a cross-sectional view showing an example of a secondary battery according to a third embodiment of the present invention, and Fig. 2 is an enlarged cross-sectional view of a portion A of the secondary battery shown in Fig. 1.
[0146] The secondary battery 100 shown in Figures 1 and 2 includes a bag-shaped exterior member 2 shown in Figures 1 and 2, an electrode group 1 shown in Figure 1, and an electrolyte (not shown). The electrode group 1 and the electrolyte are stored in the bag-shaped exterior member 2. The electrolyte (not shown) is held in the electrode group 1.
[0147] The bag-shaped exterior member 2 is made of a laminate film including two resin layers and a metal layer interposed between them.
[0148] As shown in Fig. 1, the electrode group 1 is a flat wound-type electrode group. As shown in Fig. 2, the flat wound-type electrode group 1 includes a negative electrode 3, a separator 4, and a positive electrode 5. The separator 4 is interposed between the negative electrode 3 and the positive electrode 5.
[0149] The negative electrode 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b. In the negative electrode 3, in a portion located at the outermost shell of the wound-type electrode group 1, the negative electrode active material-containing layer 3b is formed only on the inner surface side of the negative electrode current collector 3a as shown in Fig. 2. In the other portions of the negative electrode 3, the negative electrode active material-containing layer 3b is formed on both sides of the negative electrode current collector 3a.
[0150] The positive electrode 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b formed on both sides of the positive electrode current collector 5a.
[0151] As shown in FIG. 1, the negative electrode terminal 6 and the positive electrode terminal 7 are located near the outer peripheral end of the wound electrode group 1. The negative electrode terminal 6 is connected to a portion located at the outermost shell of the negative electrode current collector 3a. The positive electrode terminal 7 is connected to a portion located at the outermost shell of the positive electrode current collector 5a. The negative electrode terminal 6 and the positive electrode terminal 7 extend to the outside from an opening of the bag-shaped exterior member 2. A thermoplastic resin layer is provided on the inner surface of the bag-shaped exterior member 2, and the opening is closed by heat sealing.
[0152] The secondary battery according to the third embodiment is not limited to the secondary battery having the configuration shown in FIGS. 1 and 2, but may be a battery having the configuration shown in FIGS.
[0153] Fig. 3 is a partially cutaway perspective view showing typically another example of the secondary battery according to embodiment 3. Fig. 4 is an enlarged cross-sectional view of part B of the secondary battery shown in Fig. 3.
[0154] The secondary battery 100 shown in Figures 3 and 4 includes an electrode group 1 shown in Figures 3 and 4, an exterior member 2 shown in Figure 3, and an electrolyte (not shown). The electrode group 1 and the electrolyte are housed in the exterior member 2. The electrolyte is held in the electrode group 1.
[0155] The exterior member 2 is made of a laminate film including two resin layers and a metal layer interposed between them.
[0156] The electrode group 1 is a laminated type electrode group, as shown in Fig. 4. The laminated type electrode group 1 has a structure in which negative electrodes 3 and positive electrodes 5 are alternately laminated with separators 4 interposed therebetween.
[0157] The electrode group 1 includes a plurality of negative electrodes 3. Each of the plurality of negative electrodes 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b supported on both sides of the negative electrode current collector 3a. The electrode group 1 also includes a plurality of positive electrodes 5. Each of the plurality of positive electrodes 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b supported on both sides of the positive electrode current collector 5a.
[0158] The negative electrode current collector 3a of each negative electrode 3 includes a portion 3c on one side of which the negative electrode active material-containing layer 3b is not supported on any surface. This portion 3c serves as a negative electrode current collector tab. As shown in FIG. 4, the portion 3c serving as the negative electrode current collector tab does not overlap with the positive electrode 5. In addition, the multiple negative electrode current collector tabs (portions 3c) are electrically connected to a strip-shaped negative electrode terminal 6. The tip of the strip-shaped negative electrode terminal 6 is pulled out to the outside of the exterior member 2.
[0159] Although not shown, the positive electrode current collector 5a of each positive electrode 5 includes a portion on one side where the positive electrode active material-containing layer 5b is not supported on any surface. This portion serves as a positive electrode current collector tab. The positive electrode current collector tab does not overlap with the negative electrode 3, similar to the negative electrode current collector tab (portion 3c). The positive electrode current collector tab is located on the opposite side of the electrode group 1 to the negative electrode current collector tab (portion 3c). The positive electrode current collector tab is electrically connected to a strip-shaped positive electrode terminal 7. The tip of the strip-shaped positive electrode terminal 7 is located on the opposite side to the negative electrode terminal 6, and is drawn out to the outside of the exterior member 2.
[0160] The secondary battery according to the third embodiment includes the negative electrode according to the first or second embodiment, and therefore this secondary battery can achieve excellent cycle life characteristics and low-temperature characteristics.
[0161] (Fourth embodiment) According to a fourth embodiment, there is provided a battery pack. The battery pack according to the fourth embodiment includes a plurality of secondary batteries according to the third embodiment.
[0162] In the battery pack according to the fourth embodiment, the individual cells may be electrically connected in series or in parallel, or may be connected in a combination of series and parallel.
[0163] Next, an example of a battery pack according to a fourth embodiment will be described with reference to the drawings.
[0164] Fig. 5 is a perspective view showing an example of a battery pack according to the fourth embodiment. The battery pack 200 shown in Fig. 5 includes five cells 100a to 100e, four bus bars 21, a positive electrode lead 22, and a negative electrode lead 23. Each of the five cells 100a to 100e is a secondary battery according to the third embodiment.
[0165] The bus bar 21 connects, for example, the negative electrode terminal 6 of one cell 100a and the positive electrode terminal 7 of the adjacent cell 100b. In this way, the five cells 100 are connected in series by the four bus bars 21. That is, the battery pack 200 in FIG. 5 is a five-series battery pack. Although no example is shown, in a battery pack including a plurality of cells electrically connected in parallel, for example, the plurality of negative electrode terminals are connected to each other by a bus bar and the plurality of positive electrode terminals are connected to each other by a bus bar, so that the plurality of cells are electrically connected to each other.
[0166] The positive terminal 7 of at least one of the five cells 100a-100e is electrically connected to a positive lead 22 for external connection. Also, the negative terminal 6 of at least one of the five cells 100a-100e is electrically connected to a negative lead 23 for external connection.
[0167] The battery pack according to the fourth embodiment includes the secondary battery according to the third embodiment, and therefore this battery pack has low resistance and can achieve a high capacity retention rate.
[0168] Fifth embodiment According to a fifth embodiment, there is provided a battery pack. The battery pack includes the battery assembly according to the fourth embodiment. The battery pack may include a single secondary battery according to the third embodiment, instead of the battery assembly according to the fourth embodiment.
[0169] The battery pack according to the fifth embodiment may further include a protection circuit. The protection circuit has a function of controlling charging and discharging of the secondary battery. Alternatively, a circuit included in a device (e.g., electronic device, automobile, etc.) that uses the battery pack as a power source may be used as the protection circuit for the battery pack.
[0170] The battery pack according to the fifth embodiment may further include an external terminal for current flow. The external terminal for current flow is for outputting current from the secondary battery to the outside and / or for inputting current from the outside to the secondary battery. In other words, when the battery pack is used as a power source, current is supplied to the outside through the external terminal for current flow. When the battery pack is charged, a charging current (including regenerative energy from the power of an automobile or the like) is supplied to the battery pack through the external terminal for current flow.
[0171] Next, an example of a battery pack according to a fifth embodiment will be described with reference to the drawings.
[0172] Fig. 6 is an exploded perspective view showing an example of a battery pack according to the fifth embodiment, Fig. 7 is a block diagram showing an example of an electric circuit of the battery pack shown in Fig. 6.
[0173] The battery pack 300 shown in Figs. 6 and 7 includes a container 31, a lid 32, a protective sheet 33, a battery pack 200, a printed wiring board 34, wiring 35, and an insulating plate (not shown).
[0174] 6 is a bottomed, square container having a rectangular bottom. The container 31 is configured to be able to accommodate a protective sheet 33, a battery pack 200, a printed wiring board 34, and wiring 35. The lid 32 has a rectangular shape. The lid 32 covers the container 31 to accommodate the battery pack 200 and the like. Although not shown, the container 31 and the lid 32 are provided with openings or connection terminals for connection to an external device or the like.
[0175] The battery pack 200 includes a plurality of cells 100, a positive electrode lead 22, a negative electrode lead 23, and an adhesive tape 24.
[0176] At least one of the plurality of unit cells 100 is a secondary battery according to the third embodiment. Each of the plurality of unit cells 100 is electrically connected in series as shown in FIG. 7. The plurality of unit cells 100 may be electrically connected in parallel, or may be connected in a combination of series and parallel connections. When the plurality of unit cells 100 are connected in parallel, the battery capacity is increased compared to when they are connected in series.
[0177] The adhesive tape 24 fastens the plurality of unit cells 100. The plurality of unit cells 100 may be fixed using heat shrink tape instead of the adhesive tape 24. In this case, the protective sheets 33 are disposed on both side surfaces of the battery pack 200, the heat shrink tape is wrapped around the battery pack 200, and the heat shrink tape is then thermally shrunk to bind the plurality of unit cells 100 together.
[0178] One end of the positive electrode lead 22 is connected to the battery pack 200. One end of the positive electrode lead 22 is electrically connected to the positive electrode of one or more cells 100. One end of the negative electrode lead 23 is connected to the battery pack 200. One end of the negative electrode lead 23 is electrically connected to the negative electrode of one or more cells 100.
[0179] The printed wiring board 34 is disposed along one of the short side surfaces of the inner surface of the container 31. The printed wiring board 34 includes a positive connector 342, a negative connector 343, a thermistor 345, a protection circuit 346, wiring 342a and 343a, an external terminal 350 for supplying electricity, a positive wiring (positive wiring) 348a, and a negative wiring (negative wiring) 348b. One main surface of the printed wiring board 34 faces one side of the battery pack 200. An insulating plate (not shown) is interposed between the printed wiring board 34 and the battery pack 200.
[0180] The other end 22a of the positive electrode lead 22 is electrically connected to the positive electrode connector 342. The other end 23a of the negative electrode lead 23 is electrically connected to the negative electrode connector 343.
[0181] The thermistor 345 is fixed to one main surface of the printed wiring board 34. The thermistor 345 detects the temperature of each of the cells 100, and transmits a detection signal to the protection circuit 346.
[0182] The external terminal 350 for current supply is fixed to the other main surface of the printed wiring board 34. The external terminal 350 for current supply is electrically connected to a device present outside the battery pack 300. The external terminal 350 for current supply includes a positive terminal 352 and a negative terminal 353.
[0183] The protection circuit 346 is fixed to the other main surface of the printed wiring board 34. The protection circuit 346 is connected to the positive terminal 352 via a positive wiring 348a. The protection circuit 346 is connected to the negative terminal 353 via a negative wiring 348b. The protection circuit 346 is also electrically connected to the positive electrode connector 342 via a wiring 342a. The protection circuit 346 is electrically connected to the negative electrode connector 343 via a wiring 343a. Furthermore, the protection circuit 346 is electrically connected to each of the plurality of single cells 100 via the wiring 35.
[0184] The protective sheet 33 is disposed on both inner surfaces in the long side direction of the container 31 and on the inner surface in the short side direction that faces the printed wiring board 34 via the battery pack 200. The protective sheet 33 is made of, for example, resin or rubber.
[0185] The protection circuit 346 controls charging and discharging of the multiple cells 100. In addition, the protection circuit 346 cuts off electrical connection between the protection circuit 346 and external terminals 350 (positive terminal 352, negative terminal 353) for supplying electricity to an external device, based on a detection signal transmitted from the thermistor 345, or a detection signal transmitted from each of the cells 100 or the battery pack 200.
[0186] An example of the detection signal transmitted from the thermistor 345 is a signal that detects that the temperature of the cell 100 is equal to or higher than a predetermined temperature. An example of the detection signal transmitted from each cell 100 or the battery pack 200 is a signal that detects overcharging, overdischarging, and overcurrent of the cell 100. When detecting overcharging or the like for each cell 100, the battery voltage may be detected, or the positive electrode potential or the negative electrode potential may be detected. In the latter case, a lithium electrode used as a reference electrode is inserted into each cell 100.
[0187] The protection circuit 346 may be a circuit included in a device (such as an electronic device or an automobile) that uses the battery pack 300 as a power source.
[0188] As described above, the battery pack 300 includes the external terminal 350 for current supply. Therefore, the battery pack 300 can output a current from the assembled battery 200 to an external device and input a current from the external device to the assembled battery 200 via the external terminal 350 for current supply. In other words, when the battery pack 300 is used as a power source, the current from the assembled battery 200 is supplied to the external device through the external terminal 350 for current supply. When the battery pack 300 is charged, a charging current from the external device is supplied to the battery pack 300 through the external terminal 350 for current supply. When the battery pack 300 is used as an in-vehicle battery, regenerative energy of the vehicle's power can be used as the charging current from the external device.
[0189] The battery pack 300 may include a plurality of assembled batteries 200. In this case, the plurality of assembled batteries 200 may be connected in series, in parallel, or in a combination of series and parallel connections. The printed wiring board 34 and the wiring 35 may be omitted. In this case, the positive electrode lead 22 and the negative electrode lead 23 may be used as a positive terminal and a negative terminal, respectively, of the external terminals for current supply.
[0190] Such a battery pack is used in applications that require excellent cycle performance, for example, when a large current is drawn. Specifically, the battery pack is used, for example, as a power source for electronic devices, a stationary battery, or an on-board battery for various vehicles. An example of the electronic device is a digital camera. The battery pack is particularly suitable for use as an on-board battery.
[0191] The battery pack according to the fifth embodiment includes the secondary battery according to the third embodiment or the battery assembly according to the fourth embodiment, and therefore this battery pack can achieve excellent cycle life characteristics and low-temperature characteristics.
[0192] [Example] Examples will be described below, but the embodiments are not limited to the examples described below.
[0193] Examples 1-1 to 1-7 shown below correspond to the first embodiment described above, while Examples 2-1 to 2-8 correspond to the second embodiment described above.
[0194] (Example 1-1) A laminate cell was fabricated as a secondary battery as described below.
[0195] <Preparation of negative electrode> The negative electrode active material was lithium titanate (Li 4 Ti 5 O 12 ) powder, acetylene black as a conductive agent, polyvinylpyrrolidone (PVP: K-30 manufactured by Nippon Shokubai Co., Ltd.) as a first binder, and polyvinylidene fluoride (PVDF) as a second binder were prepared. These materials were mixed so that the mass ratio in the resulting negative electrode active material-containing layer was 100:3.0:0.10:2.5. This mixture was dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a negative electrode slurry. The solid content concentration in the negative electrode slurry was 58 mass%.
[0196] The prepared negative electrode slurry was applied to a cathode with a capacity of 1.05 mAh / cm2 per unit area on one side. 2 After coating both sides of the aluminum foil so that the thickness was 2.3 g / cm, the coating was dried to obtain a laminate. 3 The laminate was press-molded so that the laminate had a thickness of 130° C. and then dried in a vacuum at a temperature of 130° C. for 12 hours to prepare a negative electrode.
[0197] <Preparation of positive electrode> Commercially available spinel-type lithium manganese oxide (LiMn 2 O 4 100 parts by mass of lithium manganese oxide was mixed with 5 parts by mass of acetylene black as a conductive agent to obtain a mixture. Next, this mixture was dispersed in NMP to obtain a dispersion. PVdF as a binder was mixed with this dispersion in a ratio of 5 parts by mass relative to the lithium manganese oxide to prepare a positive electrode slurry. This slurry was applied to both sides of a current collector made of aluminum foil using a blade. After drying this for 12 hours at 130°C under vacuum, the density of the electrode layer (excluding the current collector) was 2.1 g / cm 3 The positive electrode was obtained by rolling the mixture so as to obtain a positive electrode.
[0198] <Preparation of electrode groups> A strip-shaped separator with a thickness of 19 μm and a width of 76 mm, consisting of 75% by weight of cellulose fiber and 25% by weight of polyester fiber (melting point 260°C), was prepared. Thirty-one rectangular negative electrodes measuring 76 mm x 56 mm were cut out from the strip-shaped negative electrode previously prepared. Thirty rectangular positive electrodes measuring 75 mm x 55 mm on one side were cut out from the strip-shaped positive electrode previously prepared. The separator was folded back every 57 mm, and 31 negative electrodes and 30 positive electrodes were alternately inserted to prepare an electrode group with a zigzag-fold separator. A positive electrode terminal and a negative electrode terminal were electrically connected to this electrode group.
[0199] <Preparation of Liquid Nonaqueous Electrolyte> A mixed solvent of propylene carbonate and diethyl carbonate (volume ratio 1:2) was prepared. Lithium hexafluorophosphate (LiPF 6) was dissolved in the aqueous solution at a concentration of 1 M. Thus, a liquid non-aqueous electrolyte was prepared.
[0200] <Preparation of laminated cell> The produced electrode group was assembled into an exterior member made of a multilayer film including multiple resin layers and metal layers interposed between these resin layers, and vacuum dried for 8 hours in an environment of 120° C. Thereafter, the previously prepared electrolyte was poured in, and the exterior member was sealed by heat sealing to produce a lithium-ion secondary battery with a design capacity of 2.5 Ah.
[0201] (Examples 1-2 to 1-4) A laminate cell was produced in the same manner as in Example 1-1, except that the content of the first binder was changed as shown in Table 1. The content of the first binder means the ratio of the mass of the first binder to the total mass of the active material particles.
[0202] (Examples 1-5 to 1-7) Except for changing the type of the first binder as shown in Table 1, a laminate cell was produced in the same manner as in Example 1-1.
[0203] (Comparative Example 1-1) A laminate cell was produced in the same manner as in Example 1-1, except that the first binder was not added.
[0204] (Comparative Examples 1-2 to 1-7) Except for changing the content of the first binder as shown in Table 1, a laminate cell was produced in the same manner as in Example 1-1.
[0205] (Comparative Examples 1-8) The negative electrode active material was monoclinic titanium dioxide (TiO 2 (B)) A laminate cell was produced in the same manner as in Comparative Example 1-1, except that powder was used.
[0206] (Comparative Examples 1-9) The negative electrode active material was a monoclinic niobium titanium composite oxide (Nb 2 TiO 7 A laminate cell was produced in the same manner as in Comparative Example 1-1, except that the cellulose acylate 1-3 powder was used.
[0207] (Comparative Examples 1-10) The negative electrode active material was monoclinic titanium dioxide (TiO 2 A laminate cell was produced in the same manner as in Example 1-1, except that the (B)) powder was used and the content of the second binder was changed as shown in Table 1.
[0208] (Comparative Example 1-11) The negative electrode active material was a monoclinic niobium titanium composite oxide (Nb 2 TiO 7 ) powder was used, and the content of the second binder was changed as shown in Table 1, and a laminate cell was produced in the same manner as in Example 1-1.
[0209] (Example 2-1) A laminate cell was produced in the same manner as in Example 1-1, except that the negative electrode slurry was prepared as follows.
[0210] The negative electrode active material was lithium titanate (Li 4 Ti 5 O 12) powder, acetylene black as a conductive agent, polyvinylpyrrolidone (PVP: K-30 manufactured by Nippon Shokubai Co., Ltd.) as a first binder, di-2-butoxyaluminum ethyl acetylacetate (manufactured by Matsumoto Fine Chemical Co., Ltd., product name A-1033R, content: 45%, remaining solvent) as an aluminum source, and polyvinylidene fluoride (PVDF) as a second binder were prepared. These materials were mixed so that the mass ratio in the resulting negative electrode active material-containing layer was 100:3.0:0.05:2.47:2.5. Here, 2.47 parts by mass of the aluminum source was added so that the amount of Al per 100 parts by mass of the active material was 0.10 parts by mass. Di-2-butoxyaluminum ethyl acetylacetate (Al(C 4 H 9 O) 2 (C 6 H 9 O 3 Since the formula weight of alkoxide is 302 and the atomic weight of Al is 27, the Al content in this alkoxide is 9%. The aluminum source was an ethanol solution with a mass concentration of 45%. From these conditions, the ratio was calculated as 0.10 / 0.09 / 0.45, and the obtained value was 2.47 [parts by mass]. The mixture obtained was dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a negative electrode slurry. The solid content in the negative electrode slurry was 58% by mass.
[0211] (Examples 2-2 to 2-5) A laminate cell was produced in the same manner as in Example 2-1, except that the content of the first binder and the amount of di-2-butoxyaluminum ethyl acetylacetate added as an aluminum source (the amount of aluminum contained in the resulting negative electrode active material layer) were changed as shown in Table 2.
[0212] (Examples 2-6 to 2-8) Except for changing the type of the first binder as shown in Table 2, a laminate cell was produced in the same manner as in Example 2-1.
[0213] (Comparative Examples 2-1 to 2-2) A laminate cell was produced in the same manner as in Example 2-1, except that the content of the first binder and the amount of di-2-butoxyaluminum ethyl acetylacetate added as an aluminum source (the amount of aluminum contained in the resulting negative electrode active material layer) were changed as shown in Table 2.
[0214] (Comparative Examples 2-3 to 2-4) A laminate cell was produced in the same manner as in Example 2-1, except that the addition of the first binder was omitted and the amount of di-2-butoxyaluminum ethyl acetylacetate added as an aluminum source (the amount of aluminum contained in the resulting negative electrode active material layer) was changed as shown in Table 2.
[0215] (Comparative Example 2-5) The negative electrode active material was monoclinic titanium dioxide (TiO 2 Except for using the (B)) powder and changing the content of the second binder as shown in Table 2, a laminate cell was produced in the same manner as in Comparative Example 2-2.
[0216] (Comparative Example 2-6) The negative electrode active material was a monoclinic niobium titanium composite oxide (Nb 2 TiO 7 ) powder was used, and the content of the second binder was changed as shown in Table 2, except that a laminate cell was produced in the same manner as in Comparative Example 2-2.
[0217] <Charge / discharge cycle test> A charge-discharge cycle test was carried out on the laminate cells produced in each of the above examples under the following conditions.
[0218] A secondary battery using lithium titanate (hereinafter referred to as LTO) with a spinel structure as the negative electrode active material and a monoclinic titanium dioxide (TiO 2The secondary battery using (B) was charged at a constant current, constant voltage (CCCV) at a voltage of 2.7 V and a current of 2 C (5 A), and then discharged at a constant current (CC) at a voltage of 1.5 V and a current of 2 C (5 A).
[0219] In addition, a secondary battery using a monoclinic niobium titanium composite oxide (hereinafter referred to as NTO) as the negative electrode active material was charged at a voltage of 2.8 V and a current of 1 C (5 A) by constant current constant voltage (CCCV) charging, and then discharged at a voltage of 1.5 V and a current of 2 C (5 A) by constant current (CC).
[0220] The secondary battery using LTO as the negative electrode active material was in an environment of 55°C, and the negative electrode active material was TiO 2 The secondary batteries using (B) or NTO were subjected to a charge-discharge cycle test in an environment of 45°C to examine the change in battery resistance at a state of charge (SOC) of 50%. Specifically, the change in resistance value before and after 2,000 charge-discharge cycle tests under the above-mentioned conditions was examined in environments of 25°C and -20°C. When examining the resistance value after 2,000 cycles, each secondary battery was discharged at 1.5V and 1C in an environment of 25°C, and then charged at 1C to adjust the SOC to 50%, and then the 10-second discharge resistance at 1C (2.5Ah) was examined in a thermostatic chamber at 25°C and -20°C.
[0221] The results are shown in Tables 1 and 2 below. Tables 1 and 2 show the negative electrode active material composition, the type and amount of the first binder, the amount of aluminum, and the type and amount of the second binder for each example of the negative electrode. Also shown are the results of the charge-discharge cycle test for each example.
[0222] In Tables 1 and 2, the column "Content (%)" of the first binder indicates the ratio of the mass of the first binder to the total mass of the plurality of active material particles contained in the negative electrode active material containing layer containing the binder, expressed as a percentage. The column "Content (%)" of the second binder indicates the ratio of the mass of the second binder to the total mass of the plurality of active material particles contained in the negative electrode active material containing layer containing the binder, expressed as a percentage. The column "25°C initial resistivity (%)" indicates the initial resistance value of the secondary battery of each example in a 25°C environment as a ratio when the corresponding value of Comparative Example 1-1 is set to 100. The column "After 2000cyc, 25°C, resistance increase rate (%)" indicates the resistance increase rate of the secondary battery of each example in a 25°C environment (ratio of the resistance value after 2,000 cycles to the initial resistance value) as a ratio when the corresponding value of Comparative Example 1-1 is set to 100. In the column "-20°C initial resistivity (%)", the initial resistance value of the secondary battery of each example in a -20°C environment is shown as a ratio when the corresponding value of Comparative Example 1-1 is set to 100. In the column "After 2000 cycles, -20°C, resistance increase rate (%)", the resistance increase rate of the secondary battery of each example in a -20°C environment (ratio of resistance value after 2,000 cycles to initial resistance value) is shown as a ratio when the corresponding value of Comparative Example 1-1 is set to 100.
[0223] [Table 1]
[0224] [Table 2]
[0225] As shown in Examples 1-1 to 1-7, in a secondary battery having a negative electrode in which active material particles contain lithium titanate having a spinel structure and a first binder contains a predetermined amount of PVP, CMC, PVA or PEG, the initial resistance in an environment of 25° C. and −20° C. is low, and the resistance increase rate is also kept low. That is, in Examples 1-1 to 1-7, excellent cycle life characteristics and low-temperature characteristics were realized.
[0226] Furthermore, as shown in Examples 2-1 to 2-8, in a secondary battery having a negative electrode in which active material particles contain lithium titanate having a spinel structure, a first binder containing a predetermined amount of PVP, CMC, PVA or PEG, and an aluminum-containing coating containing a predetermined amount of aluminum, the initial resistance in an environment of 25° C. and −20° C. was low, and the resistance increase rate was also kept low. That is, in Examples 2-1 to 2-8, excellent cycle life characteristics and low-temperature characteristics were realized.
[0227] In Comparative Example 1-1, which did not contain the first binder, and Comparative Example 1-2, in which the content of the first binder was less than 0.05 mass%, the initial resistance was relatively low, but the resistance increase rate was very high. As shown in Comparative Examples 1-4 to 1-7, as the content of the first binder increased beyond 0.50 mass%, the initial resistance also increased, and the resistance increase rate also tended to increase. Even in the case of the comparative examples in which the resistance increase rate was relatively low, when the initial resistance was high, it can be seen that the resistance value was high from the beginning to after 2000 cycles.
[0228] As shown in Comparative Examples 2-3 and 2-4, when only an aluminum-containing coating is provided without including the first binder, it is difficult to maintain a good balance between the resistance rise rate at 25° C. and −20° C. As shown in Comparative Examples 2-1 to 2-2, as the content of the first binder increases beyond 0.50 mass%, the initial resistance also increases, and there is a tendency for the resistance rise rate to also increase.
[0229] As shown in Comparative Examples 1-8 to 1-11 and Comparative Examples 2-5 to 2-6, TiO was used as the negative electrode active material. 2 When (B) or NTO was used, the resistance increase rate was high in both 25°C and -20°C environments.
[0230] According to at least one of the embodiments and examples described above, a negative electrode is provided. The negative electrode includes a current collector and an active material-containing layer supported on at least a part of the current collector. The active material-containing layer includes a plurality of active material particles, a first binder that covers at least a part of the surface of the plurality of active material particles, and a second binder different from the first binder. The plurality of active material particles includes lithium titanate having a spinel structure. The first binder includes at least one selected from the group consisting of polyvinylpyrrolidone, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, polyvinyl chloride, polyvinyl acetate, and polyacrylic acid. The ratio of the mass of the first binder to the mass of the plurality of active material particles is within a range of 0.05% by mass to 0.50% by mass.
[0231] Since at least a part of the surface of the active material particles is coated with the first binder, the formation of a coating on the surface of the active material particles due to self-discharge can be suppressed. Therefore, the increase in the positive electrode potential due to the charge-discharge cycle can be suppressed, and the deterioration of the positive electrode due to the SOC deviation and the generation of oxygen gas in the positive electrode can be suppressed. Therefore, the negative electrode according to this embodiment can achieve excellent cycle life characteristics and low-temperature characteristics.
[0232] Although several embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]
[0233] Reference Signs List 1: electrode group, 2: exterior member, 3: negative electrode, 3a: negative electrode current collector, 3b: negative electrode active material-containing layer, 3c: negative electrode current collector tab, 4: separator, 5: positive electrode, 5a: positive electrode current collector, 5b: positive electrode active material-containing layer, 6: negative electrode terminal, 7: positive electrode terminal, 21: bus bar, 22: positive electrode side lead, 22a: other end, 23: negative electrode side lead, 23a: other end, 24: adhesive tape, 31: storage container, 32: lid, 33: holder Protective sheet, 34...printed wiring board, 35...wiring, 100...secondary battery, 200...battery pack, 300...battery pack, 342...positive connector, 343...negative connector, 345...thermistor, 346...protective circuit, 342a...wiring, 343a...wiring, 350...external terminal for energizing, 352...positive terminal, 353...negative terminal, 348a...positive wiring, 348b...negative wiring.
Claims
1. A battery comprising a current collector and an active material-containing layer supported on at least a portion of the current collector, the active material-containing layer includes a plurality of active material particles, a first binder that covers at least a portion of the surfaces of the plurality of active material particles, and a second binder that is different from the first binder; the plurality of active material particles include lithium titanate having a spinel structure, The first binder includes at least one selected from the group consisting of polyvinylpyrrolidone, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, polyvinyl chloride, polyvinyl acetate, and polyacrylic acid; A negative electrode, wherein a ratio of the mass of the first binder to the mass of the plurality of active material particles is within a range of 0.05 mass % to 0.50 mass %.
2. A battery comprising a current collector and an active material-containing layer supported on at least a portion of the current collector, the active material-containing layer includes a plurality of active material particles, a first binder that covers a portion of the surface of the plurality of active material particles, a second binder that is different from the first binder, and an aluminum-containing coating that covers another portion of the surface of the plurality of active material particles, the plurality of active material particles include lithium titanate having a spinel structure, The first binder includes at least one selected from the group consisting of polyvinylpyrrolidone, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, polyvinyl chloride, polyvinyl acetate, and polyacrylic acid; a ratio of the mass of the first binder to the mass of the plurality of active material particles is within a range of 0.01 mass % to 0.50 mass %, A negative electrode in which the ratio of the mass of aluminum contained in the aluminum-containing coating to the mass of the plurality of active material particles is within a range of 0.04 mass % to 0.30 mass %.
3. The negative electrode according to claim 1 , wherein the second binder contains at least one selected from the group consisting of polyvinylidene fluoride, polyimide, and polyamide.
4. 4. The negative electrode according to claim 1, wherein a ratio of a mass of the second binder to a mass of the plurality of active material particles is within a range of 1.5 mass % to 30 mass %.
5. The lithium titanate having the spinel structure has the general formula Li 4+a Ti 5 O 12 5. The negative electrode according to claim 1, wherein a is a number within the range of -1≦a≦3.
6. A negative electrode according to any one of claims 1 to 5, A positive electrode and and an electrolyte.
7. A battery pack comprising the secondary battery according to claim 6.
8. 8. The battery pack according to claim 7, comprising a plurality of the secondary batteries, the secondary batteries being electrically connected in series, in parallel, or in a combination of series and parallel.
Citation Information
Patent Citations
Method of manufacturing electrode material, electrode material, electrode, and battery
JP2008311067A
Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2012022794A
Electrode for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and method for manufacturing electrode for nonaqueous electrolyte secondary battery
JP2012178327A
Negative electrode and nonaqueous electrolyte battery
JP2016177948A
Electrode, secondary battery, battery pack, and vehicle
JP2019169276A